2000
DOI: 10.4039/ent132505-4
|View full text |Cite
|
Sign up to set email alerts
|

MORTALITY, FEEDING INHIBITION, AND RECOVERY OF SPRUCE BUDWORM (LEPIDOPTERA: TORTRICIDAE) LARVAE FOLLOWING AERIAL APPLICATION OF A HIGH-POTENCY FORMULATION OF BACILLUS THURINGIENSIS SUBSP. KURSTAKI

Abstract: A larval population of spruce budworm, Choristoneura fumiferana (Clemens), was monitored for 5 d following aerial application of a commercial formulation of Bacillus thuringiensis Berliner subsp. kurstaki to investigate dose acquisition and expression (larval mortality, recovery, feeding, and growth) in relation to spray deposition and persistence of spray deposits. The main objective was to test if previous laboratory observations on how B. thuringiensis affects feeding and dose ingestion by spruce budworm la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…To the best of our knowledge, no information is available on feeding inhibition that occurs in gypsy moth larvae following ingestion of sublethal doses (Maczuga and Mierzejewski, 1995), a process that is known to affect dose acquisition (van Frankenhuyzen and Payne, 1993). Because both mortality and feeding inhibition depend on dose, instar and temperature (van Frankenhuyzen and Nystrom, 1987;Maczuga and Mierzejewski, 1995) and are critical determinants of spray efficacy (van Frankenhuyzen et al, 2000;Régnière and Cooke, 1998), we conducted extensive bioassays involving $21,000 larvae to investigate and quantify those relationships in a systematic fashion. We developed novel statistical approaches to analyze the complex mortality data sets.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no information is available on feeding inhibition that occurs in gypsy moth larvae following ingestion of sublethal doses (Maczuga and Mierzejewski, 1995), a process that is known to affect dose acquisition (van Frankenhuyzen and Payne, 1993). Because both mortality and feeding inhibition depend on dose, instar and temperature (van Frankenhuyzen and Nystrom, 1987;Maczuga and Mierzejewski, 1995) and are critical determinants of spray efficacy (van Frankenhuyzen et al, 2000;Régnière and Cooke, 1998), we conducted extensive bioassays involving $21,000 larvae to investigate and quantify those relationships in a systematic fashion. We developed novel statistical approaches to analyze the complex mortality data sets.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 15 years, formulations of Btk products have been improved (van Frankenhuyzen, 1995) and van Frankenhuyzen et al . (1998) demonstrated that approximately 30–35% of the toxin, resulting from an application of Foray 48B at 30 BIU/ha, persisted on foliage after 4 days, and still had insecticide proprieties (van Frankenhuyzen et al ., 2000). Thus, in the field, spruce budworm larvae might have been reinfected and recovered from several feeding inhibition periods, which could have had detrimental effects on larval growth and pupal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the results reported by Ré gniè re and Cooke (1998) and our results can be explained by the fact that larvae in the Þeld encounter Btk as discrete droplets and not as a product uniformly spread over an area as experienced on feeding disks. In the Þeld, the probability of encountering a droplet containing a lethal dose is lower at Þfth than at fourth instar because the LD 50 increases with larval age (van Frankenhuyzen et al 2000). Because feeding inhibition resulting from ingestion of a sublethal dose can hinder the acquisition of a lethal dose (van Frankenhuyzen et al 2000), it is possible that Btk droplets in the Þeld contain enough active elements to induce feeding inhibition but not to kill a Þfth-instar larva.…”
Section: Discussionmentioning
confidence: 98%
“…In the Þeld, the probability of encountering a droplet containing a lethal dose is lower at Þfth than at fourth instar because the LD 50 increases with larval age (van Frankenhuyzen et al 2000). Because feeding inhibition resulting from ingestion of a sublethal dose can hinder the acquisition of a lethal dose (van Frankenhuyzen et al 2000), it is possible that Btk droplets in the Þeld contain enough active elements to induce feeding inhibition but not to kill a Þfth-instar larva. As a possible remedy, aircraft applicator nozzles could be adjusted to spray larger droplets that would contain more active elements during the second application without increasing the application rate.…”
Section: Discussionmentioning
confidence: 98%